16-O → 8-Be + 8-Be Decay Simulation - A. Gyurjinyan
The fact that the 4He is one of the most strongly bound nuclei led to the discovery of α-clusters models in the nuclei. It is so stable that remains as a cluster in the 12C, 16O, 20Ne, etc. The nuclei that for α-clusters called α-conjugate nuclei. 13C (4He, n) reaction was used to study α -cluster states in the 16O excited levels. The measurements will improve knowledge of possible linear α-chain structure in 16O. In this work, we will present angular distribution simulation results with Geant4 for 16O-excited levels that were measured in the Ref. [8]. The simulated results will be used later on experimental data analysis that was carried out at the University of Notre Dame.
Keywords: Physics; Nuclear physics